Upaya Preventif Malaria Melalui Pembentukan Sukarelawan “Malaria Guard Kembang Ayun” (Margaku) dengan Pemanfaatkan Tanaman Serai Wangi (Cymbopongon nardus. L., rendle) di Desa Kembang Ayun. - Irawan, Putra Adi (Jurnal Pengabdian Kepada Masyarakat Pusat Unggulan Iptek Penanggulangan Stunting Berbasis Kesehatan Ibu dan Anak, 2023)
Abstract The case of malaria that occurred again in the village of Kembang Ayun is still a scourge that was thwarted by Kab. Central Bengkulu was canceled as a complete malaria area. This is a potential that needs to be carried out by the Village Partner Development Service Program as a preventive effort in dealing with malaria transmission and to support local government programs to become complete malaria areas. Community service is carried out as a form of transfer of knowledge and technology regarding the benefits of citronella in fighting malaria. There was a significant difference (p=0.00) in the level of community understanding before and after the activity. Keywords: Malaria; Cymbopogon nardus; Prevention